EVALUATION OF CLAY-TERRAZZO WASTE MIXTURE AS LINING MATERIALS IN IRRIGATION CHANNELS (Journal of Science and Technology, 2016)
This study explored the possibility of improving the quality of clay as lining material in irrigation channels by combination with terrazzo waste. Ponding method was used for measuring the seepage loss through clay lining is reduced by 35.8 percent with the addition of terrazzo waste. Regression equations were fitted for predicting seepage rate in channels lined with these materials. The combination of clay, reduces clay cracks and retards weed growth in channels.